Analysis and Proposed Improvement Permit to Work (PTW) in Chevron Geothermal Darajat Garut - Perwira, Bayu Ananta; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2014)
Abstract.Â Chevron is one of the international companies and businesses that have been run all over the world. Every worker they are committed to getting good results by way of applying the advantages of implementing innovative new technologies, responsible and get new opportunities that will be profitable growth for their success. Energy industry in the world almost all there is involvement of Chevron. Chevron to explore, create and lifting oil crude and natural gas; making power and produces geothermal energy; makes efficient energy and develop new energy sources for the future, including for advanced biofuels research. Chevron have an Operation Excellent for their safety. Operational Excellence is complex and multidimensional. It has to be in order to address all of the potential risks and causes of incidents that can impact our workforce, the environment and our assets. To help navigate this complexity, we developed the Operational Excellence Management System (OEMS). Based on the OE, then every will start the necessary work Permit To Work (PTW). However PTW requires a rather long time to process it. The methodology in this thesis is to conduct research for 2 months straight. During the study found some errors made by workers, that is giving approval is not in the work location. This can lead to the danger that arises in the work. From the results of the interview, according to the workers this is done in order to speed up work time, but on the other hand there is a danger that can arise from the actions of workers. By using the 5 whys, root cause of the problem is obtained that is the lack of workers who become Area Controller. The results of the analysis will result in improvement proposals that will be used to accelerate the process of Permit To Work (PTW) is. The results are in get is by adding people to become Area Controllers or provide training to supervisors in order to become a Controller Area.Keywords : Operation Excellent, Permit to Work (PTW), business solution, area controller